Knowing that as knowing how: a neurocognitive practicalism. - Piccinini, Gualtiero; Hetherington, Stephen (Synthese, 2025)
We defend a new, neurocognitive version of the view that knowing that is a form of knowing how and its manifestation. Specifically, we argue that knowing that P is knowing how to represent the fact that P, ground such a representation in the fact that P, use such a representation to guide action with respect to P when needed, store traces of such representations, and exercising the relevant know-how. More precisely, agents acquire knowledge via their neurocognitive systems and neurocognitive systems control organisms by building internal models of their environments and using such models to guide action. Such internal models implicitly represent how things are. When agents' implicit internal models are grounded in the fact that P and are usable for guiding action with respect to P, agents have implicit knowledge that P. When agents acquire the additional capacity to manipulate language, they also acquire the capacity to explicitly represent and express that the world is thus-and-so. When agents' explicit internal models are appropriately grounded in the fact that P and are usable for guiding action with respect to P, agents have explicit knowledge that P. Thus, both implicit and explicit knowing that P are forms of knowing how to represent that P, ground such a representation in P, use such a representation to guide action with respect to P when needed, store traces of such representations, and exercising the relevant know-how.